Narrativas do rock and roll: sociabilidades, liminaridades e performances - Santos, Lucas Monteiro dos (2018)
The following research talks about the rock and roll and phenomenons that contextualize with this theme, for example the use of the spaces for the fans e the ways of sociabilities that is possible to find in these spaces that the events happen. Talks about the historical processes of this musical style, fundamental piece for the comprehension, and about the moshpit too, corporal performance of the crowd that is completely associated with the experience to be in a rock and roll event. Field researches happened on Goiania, Goiás, and narratives were done about how these events happen and how the moshpit performance happen. The methodological path used was the cultural performance studies, that are coherent with the theme. It is possible to conclude that the ambience that rise when these events happen are full of liminarities and freedom, and all of this context ethic and aesthetical of rock and roll, moshpit and performance comes with a group of restored behaviors e a incorporated knowledge for the people that integrate the scenario and these ambiances.